Death Penalty in Indonesian Legal System: Fallibility and the Commitment to International Covenant on Civil and Political Rights - Yuber Lago; Fajar Sugianto; Syofyan Hadi (Technium Social Sciences Journal, 2023)
Indonesia as a sovereign state has inherent ability to determine its own positive law. Departing from that, Indonesia upholds death penalty in its legal system in its Criminal Code and various lex specialis laws. Death penalty has been long an issue of universal concern as it relates to the non-derogable right to life. Meanwhile Indonesia has death penalty in the national laws to maintain its own interest, it is also bound to international commitment in human rights, one of them being ICCPR which has been ratified by Law number 12 of 2005. In ICCPR, state parties are only allowed to apply death penalty for most serious crimes. This article aims to find out what are the measure for most serious crime and if Indonesian law has aligned to the measure. The research employs normative qualitative method, namely research that analyzes meanings, concepts, and characteristics in related products of law and literature by drawing on diverse strategies of inquiry. This research finds out that Indonesia indeed still has some laws not yet aligned with the most serious crime measures despite as a sovereign country, it wields power to make laws (ius poenali) and power to implement its own laws (ius puniendi).